ANALISIS POTENSI SUMBER DAYA ALAM DAN AGROWISATA BERBASIS KOMODITAS CENGKEH DI DESA OTVAI KECAMATAN ALOR BARAT LAUT - Matias Lau Mau Pating; Uriana Mabileti; Ria Boalang; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
Otvai Village is one of the villages in Northwest Alor District which is known as the largest clove producer in Alor Regency, with a land area of 198 hectares and a fairly high production every harvest season. The abundant potential of cloves makes Otvai Village have a great opportunity to develop the agro-tourism sector as a form of economic diversification based on local resources. This research aims to analyze the potential of cloves as a leading commodity, identify opportunities for agrotourism development, and review the supporting and inhibiting factors that affect its implementation. The research method used is qualitative descriptive by examining data on the potential of natural, social, economic, and village infrastructure. The results of the analysis show that Otvai Village has the main strength in clove production, a natural landscape that supports plantation tourism, and the existence of local cultural elements to support tourism activities. However, several obstacles such as damage to road infrastructure, low tourism support facilities, and lack of promotion are the main challenges in agrotourism development. This study recommends strengthening tourism village governance, improving infrastructure, and diversifying processed clove products as a community-based agro-tourism development strategy.